Analiza powstawania synkretycznych stylów zdobniczych w Azji Środkowej w VI-VIII w. n.e. na podstawie tkanin z Kotliny Turfańskiej - Kossowska, Dominika (Studia Azjatystyczne, 2015)
In the 8th century in Byzantine, Arabic and Chinese workshops weavers produced weft-faced compound twill silks (samits). These textiles were ornamented by confronted animals surrounded by pearls roundels. Usually, a rosette motive was placed between medallions. This design is a compilation of Sasanian (animals decorated with floating ribbons, pearl roundels) and Chinese patterns (symmetricalness, rosettes, ‘scrolled leaves’ motive). Its emergence took place in Central Asia. Some scholars think that it happened in Sogdiana, but the oldest samples of textiles made in the new tradition were found in Astana cemetery in Turfan Oasis (East Turkestan). Moreover, these textiles were warp-faced compound tabby – a weave technique characteristic of Chinese workshops. At first their composition was more Chinese than Sasanian, but successive Persian motives were more common. The most popular design was pearl roundels containing a confronted Pegasus standing on “a scrolled, pointed leaves in profile”. There is a large possibility that textiles found in Astana were produced locally in East Turkestan, probably in Turfan Oasis, which is located on the north branch of Silk Road. It was inhabited by a local community, but also by Sogdian and Chinese merchants. This cooperation could have led to syncretism in art and technical changes.